PENGARUH PERCEIVED VALUE TERHADAP BEHAVIORAL INTENTIONS MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI DI RESTORAN MR. PANCAKE SOLO PARAGON LIFE STYLE MALL - SL Triyaningsihadmin, Arum Permata Sari & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The objective of the research are to analyses (1) effect of perceived value to behavioral intentions, (2) effect of perceived value to consumer satisfaction, (3) effect consumer satisfaction to behavioral intentions, (4) effect of perceived value to behavioral intentions, through consumer satisfaction as the mediating variable. Population on this research are all consumer of Hartono Life Style Mall in Solo Baru. The samples of this research consist of 100 responden, taken with convenience sampling. Data collecting with questionnaire technique through validity and reliability test. To test the hypothesis, the researcher uses the path analysis, meanwhile data processing in this research using SPSS program. The result reveals that (1) perceived value have significance effect to behavioral intentions; (2) perceived value have significance effect to consumer satisfaction; (3) consumer satisfaction have significance effect to behavioral intentions; (4) there is a significance direct effect of perceived value to behavioral intentions, through consumer satisfaction as the mediating variable. The conclusion of this research that all hypothesis are supported. Keywords: perceived value, consumer satisfaction, behavioral intentions